Efektivitas Pendekatan Contextual Teaching And Learning (CTL) Dalam Meningkatkan Kemampuan Berpikir Kreatif Siswa - Susianti, Susianti; Rahmawati, Helmi; Solihah, Fatimatus (Tirai Edukasi : Jurnal Pendidikan, 2025)
This study aims to investigate the effectiveness of the Contextual Teaching and Learning (CTL) approach in improving students’ creative thinking skills. This research employed a quasi-experimental design with a pre-test and post-test control group. The population consisted of all eighth-grade students of MTS Arrahmah NW Pringgarata in the 2024/2025 academic year. Samples were selected using purposive sampling, with class VIII A as the experimental group taught using CTL and class VIII B as the control group taught using conventional methods. The instrument used was a creative thinking test based on the indicators of fluency, flexibility, originality, and elaboration, which had been validated and proven reliable. Data were analyzed through normality, homogeneity, independent t-test, and N-Gain analysis. The findings revealed that the experimental group achieved a higher mean score (80.92) compared to the control group (66.12). The t-test showed a significance value < 0.001, indicating a significant difference between the two groups. Thus, CTL is effective in enhancing students’ creative thinking skills, particularly in learning Pythagorean Theorem.